Hybrid Pulse Width Modulation for Improving Reliability of DC-Link Capacitors of NPC Inverter in Photovoltaic Systems - Jae-Heon Choi; Ui-Min Choi; Frede Blaabjerg (IEEE Access, 2024)
Reliability improvement of the Photovoltaic (PV) inverter has a high potential for reducing the cost of PV energy. The DC-link capacitor is one of the main components influencing the reliability of PV inverter systems. Various pulse-width modulation (PWM) methods have been proposed to increase the lifetime of the DC-link capacitor by reducing its ripple current. However, state-of-the-art PWM methods for reducing capacitor ripple current increase the output current THD. Nevertheless, its optimal application to achieve the target lifetime without unnecessary deterioration in output current THD has not been discussed. This paper proposes a PWM method for improving the lifetime of the DC-link capacitor of the NPC inverter. In addition, a mission-profile-based optimal application of the proposed PWM method with conventional Space Vector Modulation (SVM) called a hybrid MLZSVM method is presented for achieving the target lifetime of the DC-link capacitor with minimized negative effect on the output THD of the NPC inverter. The proposed hybrid PWM concept is verified by the case study based on an annual mission profile of the PV system. Finally, the feasibility and effectiveness of the proposed method are verified through experiments.